IMPLEMENTASI ETIKA PEJABAT PUBLIK DI SEKRETARIAT DAERAH KOTA TOMOHON - Daulima, Fabiola (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: The purpose of this study is to know the implementation. Public officials by officials within theRegional Secretariat of TomohonThe method used in this research is qualitative method. the main instrument in this study is the researcherhimself; while the information technique used is interview (interview), techniques and documentationtechniques. Qualitative data analysis technique which is an interactive modelThe results of research conducted by public officials in the Regional Secretariat of Tomohon City have beenable to implement the ethics of public officials well enough. sufficient adherence and appeasement frompublic officials or structural officials in the Tomohon City Secretariat for the code of ethics and code ofconduct applicable to all public officials specified in Law Number 5 Year 2014 on ASN, and GovernmentRegulation Number 42 Year 2004 on Corps Maintenance of Corps and Code of Ethics of Civil Servants.Keywords: Implementation, Ethics, Public Officials